2016
DOI: 10.1155/2016/3172460
|View full text |Cite
|
Sign up to set email alerts
|

Sports Nutrition Knowledge among Mid-Major Division I University Student-Athletes

Abstract: Competitive athletes have goals to optimize performance and to maintain healthy body composition. Sports nutrition is a component of training programs often overlooked by student-athletes and their coaches. The purpose of this study was to examine student-athletes' sports nutrition knowledge across sex, class level, team, and completion of prior nutrition coursework. Participants included 123 mid-major Division I university student-athletes (47 females and 76 males) from baseball, softball, men's soccer, track… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 12 publications
2
46
0
7
Order By: Relevance
“…Competitors have dreams to optimize overall performance and to hold healthful physique composition. Sports nutrition is an aspect of coaching packages regularly not noted by means of student-athletes and their coaches [21].…”
Section: Discussionmentioning
confidence: 99%
“…Competitors have dreams to optimize overall performance and to hold healthful physique composition. Sports nutrition is an aspect of coaching packages regularly not noted by means of student-athletes and their coaches [21].…”
Section: Discussionmentioning
confidence: 99%
“…Sports nutrition is a critical component of any training program; however, is often overlooked by student-athletes. For instance, it has been shown that DI athletes have inadequate sports nutrition knowledge 56 . Football players specifically also need education on sport nutrition 57 .…”
Section: Nutrition Requirements and Considerations For Afmentioning
confidence: 99%
“…In the recent years, sports NK has also been investigated through specific questionnaires [ 15 , 16 , 17 , 18 , 19 , 20 ]. Sports nutrition can be defined as the application of NK to a nutritional plan focused on meeting the nutritional requirements for physical activity, optimizing the refueling process after physical exercise, and improving athletic performance in training and competitions, as well as promoting general health and well-being [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding tools focused on sports NK, questionnaires have been validated in different populations, including both athletes and coaches [ 15 , 25 ]. Recently, some new sports NK questionnaires for adult athletes have been developed, targeting track and field [ 16 ], ultra-endurance running [ 15 , 20 ], or other sports [ 17 , 18 , 34 ]. Most of the questionnaires were validated in adults [ 16 , 17 , 34 ], and just a few in adolescents [ 15 , 35 ].…”
Section: Introductionmentioning
confidence: 99%